The impact of mechanical oesophageal deviation on posterior wall pulmonary vein reconnection. Issue 2 (22nd November 2019) - Iwasawa, Jin; Koruth, Jacob S; Mittnacht, Alexander J; Tran, Van N; Palaniswamy, Chandrasekar; Sharma, Dinesh; Bhardwaj, Rahul; Naniwadekar, Aditi; Joshi, Kamal; Sofi, Aamir; Syros, Georgios; Choudry, Subbarao; et al.
Abstract: Aims: During atrial fibrillation ablation, oesophageal heating typically prompts reduction or termination of radiofrequency energy delivery. We previously demonstrated oesophageal temperature rises are associated with posterior left atrial pulmonary vein reconnection (PVR) during redo procedures. In this study, we assessed whether mechanical oesophageal deviation (MED) during an index procedure minimizes posterior wall PVRs during redo procedures. Methods and results: Patients in whom we performed a first-ever procedure followed by a clinically driven redo procedure were divided based on both the use of MED for oesophageal protection and the ablation catheter employed (force or non-force sensing) in the first procedure. The PVR sites were compared between MED using a force-sensing catheter (MEDForce ), or no MED with a non-force (ControlNoForce ) or force (ControlForce ) sensing catheter. Despite similar clinical characteristics, the MEDForce redo procedure rate (9.2%, 26/282 patients) was significantly less than the ControlNoForce (17.2%, 126/734 patients; P  = 0.002) and ControlForce (17.5%, 20/114 patients; P  = 0.024) groups. During the redo procedure, the posterior PVR rate with MEDForce (2%, 1/50 PV pairs) was significantly less than with either ControlNoForce (17.7%, 44/249 PV pairs; P  = 0.004) or ControlForce (22.5%, 9/40 PV pairs; P  = 0.003), or aggregate Controls (18.3%, 53/289 PV pairs; P  = 0.006). However, the anterior PVR rate with MEDForce (8%, 4/50 PV pairs) was not significantly different than Controls (aggregate Controls—3.5%, 10/289 PV pairs, P  = 0.136; ControlNoForce —2.4%, 6/249 PV pairs, P  = 0.067; ControlForce —10%, 4/40 PV pairs, P  = 1.0). Conclusion: Oesophageal deviation improves the durability of the posterior wall ablation lesion set during AF ablation.